Analisis Koping dan Pertumbuhan Pasca-trauma pada Masyarakat Terpapar Konflik - Marty Mawarpury (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2018)
Prolonged conflict in Aceh has caused trauma in people who were directly affected. Aside from post-traumatic disorder, a traumatic event can bring out post-traumatic growth (PTG) too. PTG is a positive transformation that is resulted from an adaptation process of traumatic events in life. This study aimed to examine the relationship between coping and PTG. There were 55 respondents involved in this study, who were obtained by using purposive sampling technique. The sample criteria were those experiencing by themselves certain events during the conflict, men and women over 20 years old, able to read and write, and willing to be respondents for the study. Data were collected using a demographic questionnaire, Post-traumatic Growth Inventory (α = .88) and Ways of Coping Questionnaire (α= .89). The data were analyzed with the Pearson Product Moment Correlation. The analysis results showed a significant correlation between post-traumatic growth and coping (r = .523; p .01). In addition, coping ways that correlated with post-traumatic growth were seeking for social support (r = .545), distancing (r = .315), self-control and accepting (r=.274), while confronting and escape did not have a correlation with post-traumatic growth